2020
DOI: 10.1186/s41239-020-00188-0
|View full text |Cite
|
Sign up to set email alerts
|

Does mobile instant messaging facilitate social presence in online communication? A two-stage study of higher education students

Abstract: Online social presence supports student learning by making group interactions more appealing and has become a central concept in computer-mediated communication. However, questions remain over how social presence is presented in a mobile instant messaging (MIM)-facilitated environment and to what extent MIM can afford social presence compared to a threaded discussion forum. This study offers a new contribution by examining the social presence levels afforded by a MIM app (WeChat) and comparing it with a thread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 46 publications
1
8
0
2
Order By: Relevance
“…Furthermore, the availability of non-verbal cues, such as emoticons, emojis, and stickers, can convey emotions in student interactions (Tang & Hew, 2019 ) and make online conversations livelier and friendlier (Wang et al, 2016 ). Recently, Tang and Hew ( 2020 ) compared the levels of social presence between students using MIM and those using AOD and found that MIM is particularly suited to promoting expressions of emotions (affective social presence), agreement (interactive social presence), as well as phatics and support (cohesive social presence). However, this study focused solely on the social aspect of MIM use but did not examine its influence on other dimensions of students’ learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the availability of non-verbal cues, such as emoticons, emojis, and stickers, can convey emotions in student interactions (Tang & Hew, 2019 ) and make online conversations livelier and friendlier (Wang et al, 2016 ). Recently, Tang and Hew ( 2020 ) compared the levels of social presence between students using MIM and those using AOD and found that MIM is particularly suited to promoting expressions of emotions (affective social presence), agreement (interactive social presence), as well as phatics and support (cohesive social presence). However, this study focused solely on the social aspect of MIM use but did not examine its influence on other dimensions of students’ learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social presence is the degree to which participants in computer-mediated communication feel effectively connected (Swan & Shih, 2003). Social presence allows virtual community members to negotiate meaning and structure communication (Tang & Foon Hew, 2020). Without a social presence, members of a virtual community cannot successfully construct and share knowledge; social presence encourages social connectedness among members of a virtual community (Akcaoglu & Lee, 2018;Shanthi et al, 2018).…”
Section: Social Presence Theorymentioning
confidence: 99%
“…En segundo lugar, por el tiempo que actualmente los jóvenes estudiantes, invierten para establecer extensas conversaciones escritas en WhatsApp con fines concretos para el aprendizaje, que pueden redundar en consecuencias adversas en el rendimiento académico, referidas por Yeboah & Ewur (2014) como argumentaciones (Vilches y Reche, 2019). Tercero, por afectar la privacidad de los usuarios, al exponer los números telefónicos de sus dispositivos móviles en la vista pública del grupo de conversación entre estudiantes y docentes (Tang & Hew, 2020). Cuarto, por el problema de la desregulación en el uso del chat grupal, que tiende a sobresaturar de mensajes a los participantes y abrumarlos por su escasa claridad comunicativa y para la coordinación grupal hacia el desarrollo de actividades conjuntas (Vilela, Urbano y Díaz, 2015).…”
Section: Uso De Whatsapp Y Grupos De Comunicaciónunclassified